Penerapan Knowledge Mangement pada Perusahaan Food and Beverage (Studi Kasus: PT XYZ) - Vici Febriana (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
The ability of companies to manage the existing knowledge is a foundation necessary to survive. This also applies to food and beverages companies in Indonesia. Knowledge Management (KM) is an effort to improve the knowledge useful for the company. KM is not just an arrangement of knowledge, but also the management of a company with a special focus on knowledge. Difficulties in searching a recent quality document sometimes hamper the performance of employees, create an uneven distribution of documents for each division and an unavailable presentation of online information on list of quality documents that can accommodate the knowledge sharing activities among employees. The result of the research is the availability of a medium, in this case, the one that can accommodate the company's quality documents, registration documents and forums for discussion.